Fermentation of Ammonia Fiber Expansion Treated and Untreated Barley Straw in a Rumen Simulation Technique Using Rumen Inoculum from Cattle with Slow versus Fast Rate of Fiber Disappearance - Griffith, Candace L.; Ribeiro, Gabriel O.; Oba, Masahito; McAllister, Tim A.; Beauchemin, Karen A. (Frontiers in Microbiology, 2016)
The purpose of this study was to determine the effect of rumen inoculum from heifers with fast vs. slow rate of in situ fiber digestion on the fermentation of complex versus easily digested fiber sources in the forms of untreated and Ammonia Fiber Expansion (AFEX) treated barley straw, respectively, using an artificial rumen simulation technique (Rusitec). In situ fiber digestion was measured in a previous study by incubating untreated barley straw in the rumen of sixteen heifers fed a diet consisting of 700 g/kg barley straw and 300 g/kg concentrate. The two heifers with fastest rate of digestion (Fast > 4.18 % h-1) and the two heifers with the slowest rate of digestion (Slow < 3.17 % h-1) were chosen as inoculum donors for this study. Two Rusitec apparatuses each equipped with 8 fermenters were used in a completely randomized block design with 2 blocks (apparatus) and 4 treatments in a 2 × 2 factorial arrangement of treatments (Fast or Slow rumen inoculum and untreated or AFEX treated straw). Fast rumen inoculum and AFEX straw both increased (P < 0.05) disappearance of dry matter (DMD), organic matter (OMD), true DMD (TDMD), neutral detergent fiber (NDFD), acid detergent fiber (ADFD) and nitrogen (N) with an interactive effect between the two (P < 0.05). Fast rumen inoculum increased (P > 0.05) methane per gram of digested material for both untreated and AFEX straw, and reduced (interaction, P < 0.05) acetate: propionate ratio for untreated straw. Greater relative populations of Ruminococcus albus (P < 0.05) and increased microbial N production (P = 0.045) were observed in Fast rumen inoculum. AFEX straw in Fast inoculum had greater total bacterial populations than Slow, but for untreated straw this result was reversed (interaction, P = 0.013). These findings indicate that differences in microbial populations in rumen fluid contribute to differences in the capacity of rumen inoculum to digest fiber.